Bahasa Kiasan dalam Lirik Lagu Album Rosie Karya Rosé - Habsari, Melania Lintang; Ali, Ahmad Jum'a Khatib Nur (Universitas Asahan, 2025)
Figurative language is a language that cannot be taken literally. The objectives of the research are to find the types of figurative language used in the song lyrics of Rosie album by Rosé. The theory that is used in this research is the theory of figurative language by Perrine. This research used a descriptive qualitative method with Miles and Huberman analysis model. The source of the data of this research was collected from Rosé’s album “Rosie” that consists of 12 songs. The data of this study were the lyrics reflecting figurative language. The result of this research shows that there are 6 out of 12 types of figurative language applied in Rosie Album by Rosé consisting of 2 metaphors, 1 personification, 4 symbols, 2 paradoxes, 2 hyperboles, and 2 ironies. These results show that the messages and emotions in the research data tends to be constructed using reflective and artistic language style.